Enhanced Hover Control of Quad Tilt Frame UAV under Windy Conditions. (21st October 2015) - Krishnakumar, R.; Rasheed, A. Mohamed; Kumar, K. Senthil
A key research subject in the area of unmanned aerial vehicles (UAVs) is how to make them autonomous. Towards this goal, the most vital step is stabilizing the attitude of the vehicles. This paper presents the design of an autonomous control system for a hybrid UAV to enable it to carry out a stable hovering mission under external wind disturbances. The hovering capability of the hybrid UAV under windy conditions is analysed with computational fluid dynamics (CFD) and a control law is designed to stabilize the craft in the hovering position. The proposed hovering controller is verified with simulations and experiments. Finally, the flight control system is installed in a small prototype and a full transition flight test, including vertical take-off, transition from vertical flight to cruise, cruise, transition cruise to vertical mode and hover landing, is successfully accomplished.